STEPAN RUDANSCIY IS A DOCTOR, PUBLICMAN, CLASSIC OF UKRAINIAN LITERATURE (to 180 - anniversary) - Геник, С. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
In the article the question is vital way literary inheritance of classic of Ukrainian literature of Stepan Rudansciy.